2014
DOI: 10.3390/w6071873
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Household Water Treatment: Willingness to Pay Results from an Experiment in Rural Kenya

Abstract: Despite increasing availability of household water treatment products, demand in developing countries remains low. Willingness to pay for water treatment products and factors that affect demand are not well understood. In this study, we estimate willingness to pay for WaterGuard, a dilute chlorine solution for point-of-use water treatment, using actual purchase decisions at randomly assigned prices. Secondly, we identify household characteristics that are correlated with the purchase decision. Among a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…First, based on the average of HWT reported in Table 1 , only approximately 17.8% of children in our sample are reported to have access to safe drinking water, which is low. Given that it has been reported that the use of HWT is related to household characteristics, such as education level and income level [ 21 24 ], and our sample consists of a high percentage of poor households with less-educated heads of household, this low percentage is not a surprise.…”
Section: Discussionmentioning
confidence: 99%
“…First, based on the average of HWT reported in Table 1 , only approximately 17.8% of children in our sample are reported to have access to safe drinking water, which is low. Given that it has been reported that the use of HWT is related to household characteristics, such as education level and income level [ 21 24 ], and our sample consists of a high percentage of poor households with less-educated heads of household, this low percentage is not a surprise.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the recommended guidelines for routine disinfection in domestic and human healthcare settings, the following physico-chemical stress conditions were used: heat (60 °C) [ 28 ], 1.72 M sodium chloride (NaCl) [ 29 ], 150 μL of waterguard in 1 L of water [ 30 ] and 1.77 M H 2 O 2 [ 31 ]. Waterguard contains 0.178 M sodium hypochlorite (NaOCl) as the disinfectant [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined WTP for water utilisation in developing countries ( Khan et al, 2014 ; Wright, Muralidharan, Mayer et al 2014 ). In Kenya, results from a household survey revealed that households are WTP for clean water products at lower prices ( Blum et al, 2014 ). In Ethiopia, household income, education, family size, age of the respondent, water quality were reported to be associated with WTP ( Bogale & Urgessa, 2012 ).…”
Section: Introductionmentioning
confidence: 99%